Nose to Brain Delivery of Galantamine Loaded Nanoparticles: In-vivo Pharmacodynamic and Biochemical Study in Mice - Sunena; Singh, Shailendra K.; Mishra, Dina Nath (Current Drug Delivery, 2019)
Background: Presence of blood brain barrier is one of the major hurdle in drug delivery to brain for the treatment of neurological diseases. Alternative and more effective drug delivery approaches have been investigated for the drug targeting to brain in therapeutic range. Objective: The present investigation was carried out to improve the galantamine bioavailability in brain by intranasal drug delivery through thiolated chitosan nanoparticles and compared to nasal and oral delivery of its solution using pharmacodynamic activity as well as biochemical estimation. Methods: Thiolated chitosan (modified) nanoparticles were fabricated using modified ionic gelation method and intranasal delivery is evaluated by reversal of scopolamine induced amnesia and biochemical estimation of acetylcholinesterase activity in Swiss albino mice brain. Scopolamine (0.4 mg/kg, i.p.) was used to induce amnesia. Piracetam (400mg/kg, i.p.) was used as positive control. Mice were treated with galantamine solution (4mg/kg) by oral and nasal route and formulated galantamine nanoparticles (equivalent to 4mg/kg) by intranasal administration for 7 successive days and the results were compared statistically. Results: Intranasal delivery of galantamine loaded thiolated chitosan nanoparticles was found significant (p<0.05) as compared to oral and nasal administration of its solution, by pharmacodynamic study and biochemical estimation of acetylcholinesterase activity in Swiss albino mice brain. Conclusion: Significant recovery in amnesia induced mice model by intranasal administration of galantamine loaded thiolated chitosan nanoparticles established the relevance of nose to brain delivery over the conventional oral therapies for the treatment of Alzheimer's disease.
Keywords: Alzheimer' s disease (AD)